Low- vs High-Frequency Repetitive Transcranial Magnetic Stimulation as an Add-On Treatment for Refractory Depression - eche, julien; mondino, marine; haesebaert, frederic; saoud, mohamed; poulet, emmanuel; Brunelin, Jerome (Frontiers in Psychiatry, 2012)
Objectives: Repetitive transcranial magnetic stimulation (rTMS) seems to be effective as an antidepressant treatment, however, some confusion remain about the best parameters to apply and the efficacy of its association with pharmacological antidepressant treatments. Method: In a single blind randomized study14 patients with unipolar resistant depression to one antidepressant treatment were enrolled to received, in combination with venlafaxine (150 mg), either 20 sessions of 10Hz rTMS (2 000 pulses per session) applied over le left dorsolateral prefrontal cortex (DLPFC) or 20 sessions of 1 Hz rTMS (120 stimulations per sessions) applied over the right DLPFC. Results: A similar antidepressant effect was observed in both groups with a comparable antidepressant delay of action (2 weeks) and a comparable number of patients in remission after 4 weeks of daily rTMS sessions (66 vs 50 %). Conclusion: Low- and high- frequency rTMS seem to be effective as an add-on treatment to venlafaxine in pharmacological refractory major depression. Due to its short duration and its safety, low frequency rTMS may be a useful alternative treatment for patients with refractory depression.